Cleaner Production (CP) - de Oliveira Jose, José Augusto [UNESP]; Gonçalves da Cruz, Antonio José; Longati, Andreza Aparecida; Fidanza, Letícia Barbosa [UNESP] (Springer Nature, 2021)
Cleaner production (CP) is “the continuous application of an environmental strategy integrated with processes, products, and services to increase efficiency and reduce risks to humans and the environment.”